Relationship among carotenoid production, copper bioremediation and oxidative stress in Rhodotorula mucilaginosa RCL-11 - Irazusta, Verónica Patricia (2013)
Rhodotorula mucilaginosa RCL-11, a pigmented yeast isolated from a filter plant of a copper mine in the province of Tucumán, Argentina, supports high concentrations of the heavy metal Cu(II). Copper overload augmented carotenoid biosynthesis in this yeast, modifying at the same time the relative proportion of the pigments produced. Inhibition of the synthesis pathway with diphenylamine suggests an inverse relationship between carotenoid and copper biosorption by R. mucilaginosa RCL-11. The increased activity of superoxide dismutase and catalase measured under inhibition of carotenoid biosynthesis could explain these observations. Exposure to H 2 O 2 , a second oxidative stress agent, alone or in combination with Cu(II) also modified the carotenoid content, both qualitatively and quantitatively. The change in the relative proportion of the carotenoids torularhodin, torulene and beta-carotena, as well as the detection of gamma-carotene in the presence of H2O2, and Cu(II) allows to hypothesize that the carotenoids produced by R. mucilaginosa RCL-11 plays different roles in the oxidative stress response of this yeast.